Faktor yang Berhubungan dengan Kelengkapan Kunjungan Pemeriksaan Kehamilan di Puskesmas Melolo - Sri Dewi Loda Nani; Pius Weraman; Amelya B. Sir (Universitas Nusa Cendana, 2022)
Incomplete antenatal care result in risks and complications of pregnancy that are not detected early and can lead maternal and infant mortality. The main factor causing the death of pregnant women each year is due to bleeding. This can be prevented with complete and rutine antenatal care. Based on data from the Melolo Health Center, the coverage of visits by pregnant women to ANC services (K1 and K4) in 2017 amounted to 579 (K1 50% and K4 48%), in 2018 there were 542 (K1 51% and K4 45%) and in 2019 amounted to 486 (K1 62% and K4 50%) and the coverage of visits by pregnant women has not reached the target set, namely K1 100% and K4 95%. This study aims to analyze the relationship between age, knowledge, attitudes, distance to health services, and husband/family support with the completeness of antenatal care visits in the Melolo Health Center, East Sumba Regency in 2020. This type of research is an observational analytic study with a cross sectional study design. The sample in this study consisted of 66 people with the sampling technique carried out by total sampling. The data analysis used was univariate analysis and bivariate analysis using the Chi-square test. The results showed that there was a relationship between age, knowledge, attitude, and husband support with completeness of antenatal care visits. Health workers especially midwives are expected to carry out monitoring and home visits of pregnant women as well as to carry out intensive communication with pregnant women and their families so that they can carry out pregnancy checks according to standard. The husband’s role in providing motivation, attention and accompanying pregnant women in conducting ANC examinations.